Ischemic Compression dan Passive Stretching untuk Menurunkan Nyeri pada Myofascial Pain Syndrome Otot Upper Trapezius - Andi Halimah; Aco Tang; Nur Hikmah Ramadhani; Yonathan Ramba; Sri Saadiyah Leksonowati; Rahmat Nugraha (FORIKES, 2024)
Myofascial pain syndrome is a chronic muscle pain disorder characterized by the presence of trigger points. Trigger points are hypersensitive pain points located in tense muscles or what is called taut bands due to poor posture and static positions during activities. This study aimed to analyze the effectiveness of ischemic compression and passive stretching to reduce pain levels in myofascial pain syndrome of the upper trapezius muscle. The design of this study was a two-group pre-test and post-test. The sample for each group was 9 people selected using purposive sampling technique from the population. In both groups, before and after the intervention, pain levels were measured using the Visual Analog Scale. The difference in pain levels between before and after the intervention was analyzed using a paired samples t-test; while the difference in pain levels between the two groups was analyzed using an independent samples t-test. The results showed that the p value for the paired samples t-test in both groups was 0.000 each; so it was interpreted that there was a difference in pain levels between before and after the intervention, both groups that received ischemic compression and passive stretching. The pain level was lower in the post-intervention phase. The p-value for the independent samples t-test was 0.592, which means that there was no difference in the effectiveness of ischemic compression and passive stretching. In conclusion, ischemic compression and passive stretching are effective interventions to reduce pain levels in myofascial pain syndrome of the upper trapezius muscle in office workers.Keywords: myofascial pain syndrome; upper trapezius muscle; ischemic compression; passive stretching ABSTRAK Myofascial pain syndrome merupakan suatu gangguan nyeri pada otot yang bersifat kronik yang ditandai dengan adanya trigger point. Trigger point adalah titik nyeri yang hipersensitif yang terletak di otot yang menegang atau yang disebut dengan taut band karena postur tubuh yang buruk dan posisi statis saat beraktivitas. Penelitian ini bertujuan untuk menganalisis efektivitas ischemic compression dan passive stretching untuk menurunkan tingkat nyeri pada myofascial pain syndrome otot upper trapezius. Rancangan penelitian ini adalah two group pre test and post test. Sampel untuk masing-masing kelompok 9 orang yang dipilih dengan teknik purposive sampling dari populasi. Pada kedua kelompok, sebelum dan sesudah intervensi dilakukan pengukuran tingkat nyeri menggunakan Visual Analog Scale. Perbedaan tingkat nyeri antara sebelum dan sesudah intervensi dianalisis dengan paired samples t-test; sedangkan perbedaan tingkat nyeri antara kedua kelompok dianalisis dengan independent samples t-test. Hasil penelitian menunjukkan bahwa nilai p untuk paired samples t-test pada kedua kelompok masing-masing adalah 0,000; sehingga diinterpretasikan bahwa ada perbedaan tingkat nyeri antara sebelum dan sesudah intervensi, baik kelompok yang mendapatkan ischemic compression maupun passive stretching. Tingkat nyeri lebih rendah pada fase sesudah intervensi. Nilai p untuk independent samples t-test adalah 0,592, yang berarti bahwa tidak ada perbedaan efektivitas ischemic compression dan passive stretching. Sebagai kesimpulan, ischemic compression dan passive stretching merupakan intervensi yang efektif untuk menurunkan tingkat nyeri pada myofascial pain syndrome otot upper trapezius pada karyawan kantor.Kata kunci: myofascial pain syndrome; otot upper trapezius; ischemic compression; passive stretching